LATIHAN SENAM LANSIA UNTUK PENINGKATAN KUALITAS HIDUP LANSIA DI DESA KONAWEHA KECAMATAN SAMATURU KABUPATEN KOLAKA - Nur Afni; Sahmad Sahmad (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Aging is a natural process that leads to a decline in physical, cognitive, and social functions, which impacts the quality of life of the elderly. In Konaweha Village, Samaturu Subdistrict, Kolaka Regency, many elderly individuals experience limited mobility and low motivation to engage in physical activities. This study aims to implement an elderly exercise program to improve the quality of life of older adults while providing relevant health education. The method involved a site survey, participant identification, implementation of the exercise program by instructors, and evaluation using pre-test and post-test with the WHOQOL-BREF instrument. The exercises were conducted once a week for four weeks, consisting of eight main movements including warm-up, balance exercises, muscle strengthening, and cool-down. The results showed improvements in participation, mobility, balance, and social interaction among the elderly, contributing to an overall enhancement of their quality of life. This program demonstrates that elderly exercise is an effective, safe, and sustainable intervention for improving both physical and social well-being in rural communities.